EKSISTENSI PEREMPUAN MUSLIM DALAM NOVEL AKULAH ISTRI TERORIS KARYA ABIDAH EL KHALIQY KAJIAN FEMINISME EKSISTENSIALISME SIMONE DE BEAUVOIR - Kusuma, Giga Ikhlas; Sudaryani, Rina Ratih Sri (Universitas Muhammadiyah Surakarta, 2019)
ABSTRACTThis research is aimed to describe the shapes of the existence of Muslim women as a veiled women amid in the issue of Islamophobia based on the novel akulah istri teroris by Abidab el Khalieqy. The researcher use library research to collect data by reading many references. The research data were analyzed using existentialism feminist theory by simone de beauvoir. This study was descriptive qualitative with the reading method of reading as women. The results showed that the existence of Muslim women in the novel Akulah istri teroris by Abidah El Khalieqy as follows; (1) a woman who work hard for the sake of her children?s lives,(2)a women who attempt to manivest themselves as an intellectuals, (3)a women who try to transform the community into economically independent and (4) a women who refuses the others by liberating herself from her own. Keywords: women, existence, Simone de Beauvoir, freedom